Pelatihan Self Efficacy Untuk Meningkatkan Readiness for Change pada Teknisi di PT â€œXâ€ Bandung - Permadi, Azalia Cindy; Savitri, Jane; Kuntari, Indah Soca (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This research is aimed at investigating the impact of the Self-Efficacy Training to Improve Readiness for Change on the technicians of â€œXâ€ Ltd.. The research instrument used was Holtâ€™s (2003) RFCQ II questionnaire which has been modified by Puspitasari with the validity number of 0.321 to 0.807 and reability number of 0.843. The validity test of the research tool was conducted using the construct validity. The quantitative research method was employed to analyze the data obtained in this research. The research result has shown that there is a difference in the self-efficacy scores obtained by the experimental group consisting of Telkom Ltd. technicians before and after the training. A theoretical suggestion for following research is to conduct explorative research to find out other factors affecting the dimension of appropriateness. This is so that an effective training program can be arranged to increase the aforementioned dimension. A practical suggestion for Telkom Akses Ltd. is that the self- efficacy training is not only held for the companyâ€™s units in West Java Area, but also for all units in its other operating areas all over Indonesia.